Future technologies in alternative and augmented communication: a scoping review of innovations - Benevento, Alessandra Desireè; Ciulla, Giuseppe; Merlo, Gianluca (Frontiers in Communication, 2025)
IntroductionThis scoping review analyzes the convergence between augmentative and alternative communication (AAC) and new technologies, with emphasis on the role that artificial intelligence and mobile devices play in augmenting communication and social skills in individuals with complex communication needs. Technological advancements are revolutionizing AAC potential at a high velocity; thus, the aim of this study was to identify the latest technological applications and evaluate facilitators and barriers using the International Classification of Functioning, Disability and Health framework.MethodsThe review was performed according to PRISMA guidelines to identify peer-reviewed literature published between 2017 and 2025. The literature search was conducted in the four main databases: IEEE Xplore, PubMed, Web of Science, and Scopus, and found 47 eligible studies.ResultsArtificial intelligence and mobile applications are the dominant technologies that emerged. The application of artificial intelligence was categorized into four general research themes: optimization and interpretation of user input, generation of communicative content, prediction and adaptability, and communicative and technological intermediation. Mobile applications, in contrast, were categorized into: applications for integrating advanced functionalities based on intelligent systems, applications for video-based visual support strategies, applications for supporting caregivers, educators, and clinicians, and applications for multilingual and cultural support. The design of new hardware and extended reality was not extensively represented in the included literature.DiscussionThe study’s findings can serve as a scientific reference for researchers and technology developers, enabling them to leverage identified strengths, learn from current limitations, and uncover new research opportunities also considering that evidence on the real-world effects of such technologies remains scarce, with only a minority of studies using rigorous experimental designs and reporting a quantitative impact on communication skills.